Support needs of parents with preterm infants at resource-limited neonatal units in Limpopo province: A qualitative study - Thendo Mahwasane; Khathutshelo G. Netshisaulu; Thivhulawi N. Malwela; Maria S. Maputle (AOSIS, 2023)
Background: Preterm birth is often unexpected and life-threatening for the baby and/or the mother. When admitted to the hospital, midwives need to provide informational, instrumental, psycho-cultural and emotional support to enhance post-discharge care. Objectives: This study aimed to explore and describe the support provided to parents of preterm infants in preparing for post-discharge care. The study was conducted in three district hospitals in the Mopani district, South Africa. Method: A qualitative approach wherein explorative, descriptive and contextual designs were used. A non-probability, convenience sampling was used to select 23 midwives who were working in the maternity unit for at least 2 years. Data were collected through in-depth individual semi-structured interviews until data saturation was reached. The data were analysed through Tesch's open coding method. Trustworthiness was ensured through credibility, transferability and confirmability. Ethical principles adhered to were: informed consent, beneficence, right to self-determination, confidentiality and anonymity. Results: The findings revealed that parents need informational, instrumental direct supervision, and psycho-cultural and emotional support during preparation for discharge. Conclusion: Parents were unsure of their ability to care for the preterm infants after discharge and manage their own needs. The provision of informational, instrumental, psycho-cultural and emotional support needs would play a vital role in their ability to cope with their parental roles and the relationship with their infant. Contribution: The support provided to parents could build parental confidence and act as an integral part of neonatal follow-up programmes.